The role of apoptosis and the effect of epidermal growth factor on proapoptotic BNIP 3 in an experimental rat priapism model - Barut, Osman; Karakeci, Ahmet; Ozan, Tunc; Firdolas, Fatih; Pirincci, Necip; Orhan, Irfan (Tubitak Scientific & Technological Research Council Turkey, 2018)
Background/aim: This study aimed to investigate the effects of apoptosis-inducing Bcl-2/adenovirus E1B 19 kDa-interacting protein 3 (BNIP 3) and antiapoptotic epidermal growth factor (EGF) on the pathophysiology of experimental low-flow priapism. Materials and methods: Twenty-four adult Sprague-Dawley rats were divided into four equal groups. Group I was the control group. Ischemic priapism was induced for 4 h in Group II rats. In Group III, intraperitoneal EGF at 10 mu g/kg was given for 7 days before induction of ischemic priapism for 4 h. In Group IV, intraperitoneal EGF at 20 mu g/kg was given for 7 days before induction of ischemic priapism for 4 h. The western blot method was used to determine BNIP 3 expression levels and the TUNEL method was used to determine the apoptotic cells in the cavernosal tissue samples. Results: Although BNIP 3 expression levels were significantly higher in all three study groups compared to the controls, BNIP 3 was significantly higher in EGF-administered groups when compared to Group II (P < 0.05). The TUNEL score of group II was significantly higher than those of the other groups. Conclusion: Decreased apoptosis in cavernosal tissues obtained by antagonizing the apoptotic effect of BNIP 3 with EGF may facilitate the development of new conservative treatment methods via those pathways.
Keywords: Apoptosis; BNIP 3; epidermal growth factor; priapism; rat